Epidemiological analysis of the incidence of endometrial hyperplasia in a large city of Kazakhstan - Imashkyzy, Imasheva Bayan; Adilkhanovich, Kamaliev Maksut; Notanovich, Lokshin Vyacheslav; Viktorovna, Kiselyova Marina; Dzhambylbayevna, Turekhanova Aizhan; Ernazarovna, Jexembekova Alfiya; Malika, Uteshova; Mukhtarkyzy, Saparaliyeva Aizhan (Intelektual Pustaka Media Utama, 2025)
Endometrial hyperplasia (EH) is an abnormality of uterus, characterized by excessive proliferation of endometrium, and in case of lack of timely diagnostics and treatment, it may rapidly progress to endometrial cancer (EC). According to the World Cancer Research Fund, EC ranks 6th among all female malignancies in the world. EC takes the 3rd place in the Republic of Kazakhstan according to the state statistics. However, there is no determining statistical data on dynamics of EH incidence in our region, which will show the extent of exposure of the population to this disease. Therefore, this research provides assessment and analysis of all registered cases of EH from the Republican Center for Electronic Healthcare for the period from 2012 to 2022 for presentation of accurate and correct information on the trends of EH incidence and its histologic types, taking into account age differences of the female population of our city. The study has showed the increase of indicators of incidence of EH, especially, non-atypical endometrial hyperplasia (NAEH) and atypical endometrial hyperplasia (AEH). It was found that the peak incidence of EH occurred in the age group of 65-69 years, where the main increase was due to an increase in number of cases of NAEH. The age group of 45-49 years is at the peak of the incidence of AEH. The conducted research has identified the trends of EH incidence, reflecting population changes in the EH risk factors, and that requires their comprehensive study for development of strategies of treatment and prevention measures.